Development of improved plantain/banana germplasm with black sigatoka resistance - Ortíz, R.; Vuylsteke, D.R.; Ferris, R. (1994)
Variety improvement of plantain and banana (Musa spp.) is based on genetic diversity, which provides the basis for selection gain. This paper reviews result obtained by the Plantain and Banana Improvement Programme (PBIP) of the International Institute of Tropical Agriculture in the development of improved plantain germplasm (TMPx) with stable yield, improved suckering, short stature and black sigatoka resistance. The success of this programme was basedon the significant genetic variability found for most growth and yield parameters as well as black sigatoka reponse. Several major loci influencing the phenotypic expression for plant height, suckering, fruit development and black sigatoka resistance were identified. Environment and genotype-by-environment effects were analyzed. The results indicated that multilocational trial are necessary to assess yield stability of plantain-banana hybrids across environments in the same agroecological zone. Two exceptional black sigatoka-resistant tetraploid clones TMPx 1658-4 and TMPx 548-9 were identified as high and stable yield genotypes. Currently, this improved Musa germplasm with black sigatoka resistance is being assessed for postharvest characteristics to determine fruit palatability and durability.